2017
DOI: 10.3892/etm.2017.5364
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of peripheral blood cluster of differentiation 4+ adenosine triphosphate activity and CYP3A5 genotype to determine the pharmacokinetics, clinical effects and complications of tacrolimus in patients with autoimmune diseases

Abstract: Abstract.A total of 25 patients with autoimmune diseases receiving tacrolimus were screened using a peripheral blood cluster of differentiation 4 + adenosine triphosphate (ATP) activity assay (IMK assay) between October 2013 and July 2014. The autoimmune diseases of patients were as follows: Rheumatoid arthritis (n=15), lupus nephritis (n=6), ulcerative colitis (n=2) and myasthenia gravis (n=2). Patients were divided into two groups based on CYP3A5 genotype [expression of *1 allele: Expressor (EX; n=6) and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…The results showed that in MN patients, TAC blood concentrations of CYP3A5 expressers are comparatively lower than those of CYP3A5 non-expressers at different time points (≤1 month, 1–6 months, and ≥6 months) after medication administration. The findings are consistent with the effect of different CYP3A5 * 3 genotypes on TAC in transplant patients ( Muraki et al, 2018 ). However, the impact of the CYP3A5*3 genetic polymorphism on the effectiveness of TAC therapy in patients with MN remains uncertain.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that in MN patients, TAC blood concentrations of CYP3A5 expressers are comparatively lower than those of CYP3A5 non-expressers at different time points (≤1 month, 1–6 months, and ≥6 months) after medication administration. The findings are consistent with the effect of different CYP3A5 * 3 genotypes on TAC in transplant patients ( Muraki et al, 2018 ). However, the impact of the CYP3A5*3 genetic polymorphism on the effectiveness of TAC therapy in patients with MN remains uncertain.…”
Section: Discussionsupporting
confidence: 89%
“…These colorectal cancer responsible genes might be candidate genes for CD. Recently, increasing evidence demonstrated that CXCL5 [379], S100A8 [380], LCN2 [381], CXCL1 [382], S100A9 [383], CXCL9 [384], CXCL11 [385], CXCL10 [386], NCF2 [387], SLC11A1 [388], GDF15 [389], IL1RN [390], STAT1 [391], CYP27B1 [392], SOCS3 [393], TLR8 [394], CD55 [395], ADGRG3 [396], CCL3 [397], FCGR2A [398], CCL2 [399], CD14 [400], IGFBP2 [401], PCSK9 [402], IDO1 [403], FOXP3 [404], CD163 [405], CCL7 [406], TLR2 [407], CCR2 [408], IL20RA [409], S100P [410], ADAMTS1 [411], TIMP1 [412], ICAM1 [413], IFNG (interferon gamma) [414], TREM2 [415], APOE (apolipoprotein E) [416], CCR1 [417], IL6 [418], CTHRC1 [419], PDCD1LG2 [420], CCL4 [421], IL11 [422], COL1A1 [423], MMP2 [424], IL1A [425], CD24 [426], POSTN (periostin) [427], GZMB (granzyme B) [428], BCL2A1 [429], CSF2 [430], TDO2 [431], CTLA4 [432], PADI4 [433], MPO (myeloperoxidase) [434], HP (haptoglobin) [435], MUC5B [436], MMP7 [437], PON3 [438], ABHD6 [439], AICDA (activation induced cytidine deaminase) [440], UGT1A6 [441], CYP2D6 [442], CYP3A5 [443], DGAT1 [444], FCRL4 [445], SLC22A4 [446], DPP4 [447], ACE (angiotensin I converting enzyme) [448], SLC5A11 [449], VIPR1 [450], FCRL3 [451], CD160 [452] and IL22RA2 […”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic systemic disease, mainly characterized by synovitis, synovial hyperplasia, pannus formation, and osteochondral destruction ( Muraki et al, 2018 ; Shiraishi et al, 2017 ). Due to the joint dysfunction caused by RA, patients often have limited activities, and the quality of life is seriously reduced ( Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%